Influence of student's non-cognitive trait and cognitive heuristic on the entrepreneurial venture's initial set up decision - Naila Aaijaz; Mohamed Dahlan Ibrahim; Ghazali Ahmad; Shaliza Abdul Razit (2012)
The present studyis designed to examine the influence of non-cognitive characteristics and cognitive heuristic i.e learned by experience, demographic factors, entrepreneurial and others on the entrepreneurial initial set up decision.Research inference is derived from the samples of 150 entrepreneurial program students during the period 2011-2012 selected from University Malaysia Kelantan (UMK), University Putra Malaysia (UPM) and University Utara Malaysia (UUM).Previous studies have endeavored to measure the effects of one more variables on the key decision taking ability of entrepreneurs, but while the main implication of this study is to collect all related variables in an integrated model and to investigate cumulative effects of these variables on the entrepreneurial key decision taking ability of entrepreneurs. The present study findings are based on the cumulative effects of entrepreneur's non-cognitive attributes and cognitive notions and heuristics on the ability of entrepreneurial key decision taking ability which have not been investigated in previous studies yet.